Domestic dogs (Canis lupus familiaris) are sensitive to the correlation between pitch and timbre in human speech - Sturdy, Sasha K.; Smith, David R. R.; George, David N. (Animal Cognition, 2021)
Abstract The perceived pitch of human voices is highly correlated with the fundamental frequency ( f 0) of the laryngeal source, which is determined largely by the length and mass of the vocal folds. The vocal folds are larger in adult males than in adult females, and men’s voices consequently have a lower pitch than women’s. The length of the supralaryngeal vocal tract (vocal-tract length; VTL) affects the resonant frequencies (formants) of speech which characterize the timbre of the voice. Men’s longer vocal tracts produce lower frequency, and less dispersed, formants than women’s shorter vocal tracts. Pitch and timbre combine to influence the perception of speaker characteristics such as size and age. Together, they can be used to categorize speaker sex with almost perfect accuracy. While it is known that domestic dogs can match a voice to a person of the same sex, there has been no investigation into whether dogs are sensitive to the correlation between pitch and timbre. We recorded a female voice giving three commands (‘Sit’, ‘Lay down’, ‘Come here’), and manipulated the recordings to lower the fundamental frequency (thus lowering pitch), increase simulated VTL (hence affecting timbre), or both (synthesized adult male voice). Dogs responded to the original adult female and synthesized adult male voices equivalently. Their tendency to obey the commands was, however, reduced when either pitch or timbre was manipulated alone. These results suggest that dogs are sensitive to both the pitch and timbre of human voices, and that they learn about the natural covariation of these perceptual attributes.